Bystander intervention in the context of abusive supervision : Effects of power distance orientation and gender - Arman, Gamze (Colegio Oficial de Psicólogos de Madrid, 2020)
This study focused on the perceptions and reactions of observers in abusive supervision situations, with regard to the premises of the Bystander Intervention Framework. A 2 x 2 x 2 design was used based on observer's, perpetrator's, and victim's gender. Several vignettes for four different perpetrator-victim dyads (e.g., female perpetrator-male victim) were developed. Participants (N = 197) read these vignettes consecutively over five days and finally were asked to evaluate the perceived acceptability of the abusive supervision, and rate their willingness to help the victim. Results revealed that higher power distance orientation increased perceived acceptability of abusive supervision, and higher perceived acceptability increased avoidance of help while simultaneously decreasing willingness to provide direct or indirect help. The gender of the perpetrator was critical in perceived acceptability, whereby male observers were more tolerant toward male perpetrators. In addition, the gender of the victim was a determinant of the type of help given.